The hypothesis of the prefigurative culture of digital generation Y, Z in the Post-Soviet space (Journal of Philosophy Culture and Political Science, 2020)
The article is devoted to the analysis of the term of prefigurative culture in the context of Strauss-Howe’s generational theory. The analysis, in particular, states that innovative technologies are changingthe very nature of man and his social connections in societies that focus on further improving andintroducing innovative digital technologies in the fields of social communications, professional activities,education of the younger generation, science and other fields. The aim of the research is to put ahypothesis of the prefigurative digital culture of Generation Y, Z and to try to answer the question of thepossibility of changing the fundamental characteristics of the human being included in the new digitalreality. The paradox of its essence lies in its belonging to the world of people and to the world of theinhuman forces of nature. The anthropological approach assesses degree and result of the interactionbetween technology and man.Key words: prefigurative culture, generation Y, generation Z, digital culture, virtual reality, CentralAsian countries.